2010
DOI: 10.1002/bip.21555
|View full text |Cite
|
Sign up to set email alerts
|

CGG repeats associated with fragile X chromosome form left-handed Z-DNA structure

Abstract: This work is a continuation of our effort to determine the structure responsible for expansion of the (CGG)(n) motif that results in fragile X chromosome syndrome. In our previous report, we demonstrated that the structure adopted by an oligonucleotide with this repeat sequence is not a quadruplex as was suggested by others. Here we demonstrate that (CGG) runs adopt another anomalous arrangement-a left-handed Z-DNA structure. The Z-DNA formation was induced by high salt and millimolar concentrations of Ni(2+) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 44 publications
2
30
0
Order By: Relevance
“…This was the first proof of the Watson-Crick model, which was questioned at that time. [22][23][24] RNA is also able to transform into the left-handed structure, 25 and the A-Z switch may be linked to its function. 3) or in a combination of salt and alcohol.…”
Section: Alternating Purine-pyrimidine Sequences Z Formmentioning
confidence: 99%
“…This was the first proof of the Watson-Crick model, which was questioned at that time. [22][23][24] RNA is also able to transform into the left-handed structure, 25 and the A-Z switch may be linked to its function. 3) or in a combination of salt and alcohol.…”
Section: Alternating Purine-pyrimidine Sequences Z Formmentioning
confidence: 99%
“…A tenth polyalanine expansion disorder associated with the Zic family member 3 gene [ ZIC3 ; MIM# 300265] and leading to X-linked heterotaxy with VACTERL association has recently been described [Wessels et al, 2010]. Most of these microsatellite sequences have been shown to be capable of adopting specific secondary structures (non-B DNA), including hairpin-loops, three-(triplex) and four-stranded (quadruplex) structures and left-handed Z-DNA [Lopez Castel et al, 2010; Mirkin, 2007; Renciuk et al, 2011; Wells and Ashizawa, 2006]. Below, we review some of the most compelling evidence in support of a role for DNA secondary structures in either microsatellite expansion and/or the process of pathogenesis.…”
Section: Microsatellite Mutationmentioning
confidence: 99%
“…However, the mechanisms by which expanded (CGG•CCG) repeats induce methylation remain unclear. (CGG•CCG) repeats have been shown to fold into hairpin-loops [Amrane and Mergny, 2006; Darlow and Leach, 1998], quadruplexes [Khateb et al, 2004; Usdin and Woodford, 1995], left-handed Z-DNA [Renciuk et al, 2011], to possess inherently high flexibility (bending) [Bacolla et al, 1997] and are predicted to sustain stable ‘bubbles’ despite their high CG content [Alexandrov et al, 2011]. In vitro , the ability of DNA methyltransferase 1 (DNMT1) to methylate (CGG•CCG) repeats increases with increasing negative supercoiling [Bacolla et al, 2001].…”
Section: Microsatellite Mutationmentioning
confidence: 99%
“…Many microsatellite motifs can adopt unusual DNA conformations such as hairpins, quadruplexes, parallel duplexes and even left-handed Z-DNA [8][10]. Several decades ago it was shown that poly(dC-dA).poly(dT-dG) motifs can adopt a Z-DNA conformation [11].…”
Section: Introductionmentioning
confidence: 99%